НАСЛІ ДУВАННЯ ЯК ОСНОВНИЙ МЕТ ОД НАВЧАННЯ У ВАЛЬДОРФ СЬКІЙ ДОШКІЛ ЬНІЙ ОСВІТІ - Litvin, L. (Continuing Professional Education: Theory and Practice, 2019)
The imitation as the important method of education and development in the early childhood is analyzed in the article; the importance of the imitation for development of the adroitness, skills and abilities, masterfulness, creative and esthetical capabilities of a child is emphasized; it is defined that it is necessary for the teacher to bring up and to educate himself; the main demands for the Waldorf kindergarten teacher are observed.